Dedicated breast computed-tomography in women with a personal history of breast cancer: A proof-of-concept study. Issue 158 (January 2023) - Formaz, Eméline; Schmidt, Cynthia; Berger, Nicole; Schönenberger, Amadéa L.N.; Wieler, Jann; Frauenfelder, Thomas; Boss, Andreas; Marcon, Magda
Highlights: Breast CT has potential for imaging surveillance in patients after breast cancer. Confidence for image evaluation in breast CT was equal/superior to mammography. Post-operative material artifacts do not usually compromise CT-image evaluation. Abstract: Purpose: To compare the subjective image quality assessment using B-CT and digital mammography in women with personal history of breast cancer (PHBC). Method: In this retrospective study 32 patients with PHBC were included. Each patient had undergone a B-CT examination and a previous mammogram in a time interval of less than 18 months between the two examinations. Two radiologists evaluated the two examinations independently with regard to the presence of lesions, BI-RADS classification, level of confidence for the overall exam interpretation, scar evaluation and image quality including image degradation due to clip artifacts. Level of confidence and image quality were assessed using a 5-point Likert scale. A p -value of less than 0.01 was considered statistically significant. Results: Thirty-seven operated and 27 non-operated breasts were included. Confidence for the overall interpretation with B-CT was equal or superior to mammography in 63 cases (98.4 %) for reader 1 and in 58 cases (90.6 %) for reader 2 (p <.001). Confidence for scar evaluation with B-CT was equal or superior to mammography in all cases for reader 1 and in 34 cases (91.9 %) for readers 2 (p <.001). One case with local recurrence in B-CT was identified by both readers and no false positive findings were reported. A moderate to high image degradation due to beam-hardening artifacts has been reported by both readers in 29.4 % of cases due to surgical clips in the B-CT volume. Conclusions: B-CT in patients with PHBC provides high quality images that can be evaluated with confidence equal or superior to mammography.